Charcoal Suspension Tattoo: A New Technique for Intraoperative Detection of Small Tumors of the Parotid Gland. (July 2016) - Tirelli, Giancarlo; Cova, Maria Assunta; Boscolo-Rizzo, Paolo; Da Mosto, Maria Cristina; Makuc, Elisa; Gardenal, Nicoletta
Objective: The current surgical trend in the treatment of pleomorphic adenomas of the parotid gland is to limit the extent of resection. This raises the need to correctly identify the mass within the normal parenchyma so as to avoid dissecting the entire superficial lobe of the gland. We describe ultrasound-guided tattooing as a technique to facilitate identification and excision of parotid pleomorphic adenomas. Methods: We reviewed 23 consecutive patients with pleomorphic adenoma of the parotid gland. All patients underwent ultrasound-guided tattooing of the lesions with a charcoal suspension. Baseline tumor and patients' characteristics, major and minor complications, and subjective tolerance to the procedure were recorded. We assessed the number of intralesionally marked masses and the percentage of intraoperatively detected marked lesions. Results: The injection was well tolerated. No major complications were recorded. In 2 cases (9%), a transient increase in lesion size was observed. No other minor complications were encountered. Charcoal was found inside the tumor in 19 cases (83%). In 4 cases (17%), it was found in the tissues above the lesion. Twenty-three lesions were intraoperatively detected (100%) and dissected. Conclusion: Charcoal suspension tattooing is safe and well tolerated for the detection of small pleomorphic adenomas during parotid surgery.